Design and Synthesis of 5‐Aryl‐substituted Phenylpyrimidine‐2, 4‐diamine Derivatives as Novel Mer and Tyro3 Kinase Inhibitors. (13th December 2020) - Kim, Yeonji; Lee, Kyung Won; Yeom, Hyesu; Kim, Miok; Lee, Yeon Kyung; Lee, Joo‐Youn; Hwang, Jong Yeon; Min, Youngki; Ryu, Do Hyun; Lee, Chang Hoon; Cho, Sung Yun
Abstract : 5‐Aryl‐substituted (piperdin‐4‐yl)pyrimidine‐2, 4‐diamine derivatives were synthesized and their inhibitory activities were evaluated against TAM kinase (Tyro3, Axl, Mer), respectively. Detailed SAR studies on the fifth position of pyrimidine could lead to the discovery of potent and selective TAM kinase inhibitor. Compounds 6f, 7b, and 7f exhibited potent inhibitory activity and excellent selectivity toward Axl, Tyro3 and Mer kinases. Molecular docking studies corroborated that slight changes of substituents induced dramatic structural change of Met596, 623, 674 backbone carbonyl and amide in the hinge region of Axl, Tyro3, Mer, and resulted in different binding poses of 6f, 7b, and 7f, respectively. It was identified as a strong possibility to control selectivity by structural modification of phenyl substituents of pyrimidine as a new class of TAM kinase inhibitors. Abstract : Mer kinase inhibitor